Recombinant neorudin and its active metabolite hirudin: the fate in vivo of a novel anticoagulant drug - Li, Qiang; Liu, Yubin; Ren, Boyuan; Jin, Jiayan; Zhang, Lin; Wu, ChuTse; Jin, JiDe (Frontiers in Pharmacology, 2024)
Thrombosis, a prevalent condition, can provoke severe health issues like acute coronary syndrome (ACS), deep vein thrombosis (DVT), and pulmonary embolism (PE). The rising incidence of these diseases annually significantly impacts patient well-being and poses a substantial burden on healthcare systems. Recombinant neorudin is a developing anticoagulant drug for thrombotic diseases whose phase I clinical trials has been completed. The distribution pattern of it and its active metabolite, hirudin, in thrombi, blood surrounding the thrombus and peripheral blood remains uncertain. This study explored their distribution using a rat arteriovenous bypass thrombosis model, revealing higher neorudin levels in blood surrounding the thrombus and elevated hirudin concentrations in thrombus. Recombinant neorudin significantly increased Thrombin Time (TT) in both plasma surrounding the thrombus and peripheral blood, and reduced the wet weight of the thrombus. The results above demonstrated the anticoagulant and antithrombotic efficacy of recombinant neorudin in vivo. Give the distribution pattern of neorudin and hirudin, we hypothesized that neorudin was cleaved at the site of thrombus formation to produce hirudin, leading to the rapid accumulation of hirudin within local thrombi and resulting in a higher concentration inside the thrombus. This insight was crucial for understanding the action mechanisms of anticoagulants in thrombosis management and provided a valuable guidance for therapeutic strategies in treating thrombotic diseases.